PERCEPTION OF FISH FARMER ABOUT FISH CULTIVATION IN SULIGI VILLAGE, PENDALIAN IV KOTO SUBDISTRICT, ROKAN HULU REGENCY, RIAU PROVINCE - Vera sofiana; Zulkarnaini '; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Research about perception of fish farmer in fish cultivation was done at oktober 2015 in suligi village, pendalian IV koto subdistrict, rokan hulu regency, riau province. The purpose of this research is to describe of fish farmer and fish cultivation characteristics and also to analyze the perception of fish farmer to fish cultivation which comprised by opinion, estimation and suggestion in suligi village. After that analyze the relation between perception and characteristic of fish cultivation. The method in this research is survey method.Based on result of research, knowing that fish farmer is in productive age but cultivation experience is classified in low. Financial capital output is low whit marketing just done in suligi village. The perception of fish farmer about fish cultivation totality has score 2.232 on middle categories. The relationship of financial capital and marketing to fish farmer perception is significant. It is has same direction and has significantly relationship.Keyword : perception, farmer, fish cultivation, suligi